PEMBINAAN SIKAP SPIRITUAL KEAGAMAAN MELALUI PEMBELAJARAN TAREKAT QADIRIYAH NAQSABANDIYAH - Isop Syafe'i; Ai Samrotul Fauziyah (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
This study departs from the phenomenon in the school environment that incorporates TQN lessons on local content so researchers want to know which ones support the development of spiritual attitudes through TQN learning to make students good in their religious-spiritual attitudes. This research uses a qualitative approach using descriptive methods. This research was conducted by explaining or analyzing data obtained from MTs Serba Bakti Suryalaya. Data collection techniques using in-depth interviews, observation, documents, and questionnaires. Data analysis techniques in this study by analyzing all available data from various sources through, in-depth interviews and documentation studies using field notes. Data analysis techniques in this study were carried out qualitatively to analyze data from interviews and documentation instruments. The results showed that; 1) fostering religious-spiritual attitudes through learning TQN aims to realize students who have faith, practice worship and have good morals, 2) implementation of fostering religious-spiritual attitudes through TQN learning is done by creating effective and conducive classes, internalizing values, for example habituation , habituating and forming attitudes and behaviours, 3) supporting factors are adequate facilities and infrastructure, determination and enthusiasm of all school components, environment and support of student guardians and inhibiting factors are the psychological and psychological aspects of students and student motivation and interest to participate in TQN Learning , 4) the success of cultivating religious-spiritual attitudes through TQN learning has effectively been able to encourage students to be better viewed from measurements based on the success obtained after studying TQN in the form of problem solving, high emotional resilience, inner calm, self control i, understand your fairy and find who you are. Thus, in an effort to improve religious-spiritual attitudes, other schools can also apply the learning of the qadariyah naqsabandiyah order.